DIAGNOSIS SYSTEM DESIGN OF DEPRESSION AND ANXIETY WITH NAÃVE BAYES METHOD - Jennie Angelyn; Ramalia Noratama Putri (Journal of Applied Business and Technology, 2021)
Depression and Anxiety are mental illness that arise in the presence of depression and anxiety from within the individual. The depression having features them level a dramatic decline to an interest, trouble sleeping and eat, the guilt or feel having no value self, and usually followed by a feeling of agitated, uneasiness is the norm reasonable like when we will do appearance in front of people. However, for the level of anxiety that must be considered is when the individual experiences an excessive intensity of anxiety unlike other normal individuals. The method in the system used to diagnose depression and anxiety is the Naïve Bayes Method. The process of using the naïve bayes method by using 50 correspondent data then taking 5 samples from the diagnostic results to prove the accuracy of the data generated after being diagnosed, this method can provide diagnosis, then provide therapy as an initial preventive step for sufferers, and as a solution to suppress therapy costs for suffers and sufferers’ choice as the first step before seeing the experts in person.